Editorial for the Special Issue on 3D Printing for Tissue Engineering and Regenerative Medicine - Vahid Serpooshan; Murat Guvendiren (Micromachines, 2020)
Three-dimensional (3D) bioprinting uses additive manufacturing techniques to fabricate 3D structures consisting of heterogenous selections of living cells, biomaterials, and active biomolecules [...]